Hydrometallurgical recycling of lithium-ion batteries by reductive leaching with sodium metabisulphite - Vieceli, N. (2018)
ABSTRACT: The hydrometallurgical extraction of metals from spent lithium-ion batteries (LIBs) was investigated. LIBs were first dismantled and a fraction rich in the active material was obtained by physical separation, containing 95% of the initial electrode, 2% of the initial steel and 22% of plastic materials. Several reducers were tested to improve metals dissolution in the leaching step using sulphuric acid. Sodium metabisulphite led to the best results and was studied in more detail. The best concentration of Na2S2O5 was 0.1 M. The metals dissolution increased with acid concentration, however, concentrations higher than 1.25 M are unnecessary. Best results were reached using a stirring speed of 400 min(-1). The metals leaching efficiency from the active material (Li, Mn, Ni, Co) increased with the temperature and was above 80% for temperatures higher than 60 degrees C. The dissolution of metals also rose with the increase in the liquid/solid ratio (LAS), however, extractions above 85% can be reached at LAS as lower as 4.5 L/kg, which is favourable for further purification and recovery operations. About 90% of metals extraction can be achieved after only 0.5 h of leaching. Sodium metabisulphite can be an alternative reducer to increase the leaching of Li, Mn, Co, and Ni from spent LIBs.